Endodontic Management of Dentinogenesis Imperfecta Using Guided Endodontics: A Case Report - Rahmatian, Mohammadreza; Kazemi, Ali; Dianat, Omid; Safi, Yaser (Iranian Endodontic Journal, 2024)
Pulp canal calcification (PCC) is common in patients with dentinogenesis imperfecta (DGI). We present endodontic management of multiple anterior and posterior teeth with PCCs in a patient with DGI type II using guided endodontics. A 26-year-old female patient was diagnosed with DGI type II. Clinical examination revealed palatal cusp fracture in tooth #13, microcracks in tooth #14, and a sinus tract in the maxillary right buccal vestibule related to tooth #13. Periapical radiographs revealed PCCs in all teeth, and periapical radiolucencies in several teeth. Due to difficult negotiation of canal orifices, guided endodontic approach was planned. Cone-beam computed tomography (CBCT) was requested and obtained. Intraoral scanning was performed, and CBCT and intraoral scanning data were superimposed. A template was designed and 3D printed. The root canal orifices were successfully negotiated and endodontic treatments were successfully accomplished. At the 1-year follow-up, the endodontically treated teeth were asymptomatic, and periapical lesions were healing.